Analisis Kompetensi Karyawan Terhadap Kinerja Karyawan di Era Digital - Muhammad Rizki Faudzil Adhim; Enjang Suherman (Pusat Riset dan Inovasi Nasional, 2024)
In the digital era, technological developments have brought significant changes to the world of work, requiring companies to adapt quickly to remain competitive. Employee competency is a key factor in this adaptation process, because adequate competency can improve employee performance and, in turn, overall company performance. This research analyzes the importance of employee competency in improving performance in the digital era, with a focus on digital skills, adaptability, and soft skills such as communication and collaboration. The results of interviews with human resource managers and employees show that the development of digital skills, adaptability, and company support in continuous learning are very important to achieve optimal performance. Companies need to invest in comprehensive training programs and create a work environment that supports employee competency development. In this way, employees can adapt quickly to technological changes, work more effectively, and contribute optimally to the company's success